Investigasi atas revaluasi aset, penyajian laporan keuangan, dan kualitas auditor berbasis mandatory IFRS - Nurmala Ahmar (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2018)
Revaluation of asset is not carried out by the company in Indonesia today. This prompted Finance Minister Regulation Number 191/PMK.010/2015 on revaluation for tax purposes. Revaluation of assets in general purpose is to increase the firm's value and presents an account at the real values. This research investigating the activity of asset revaluation carried out by a public company in Indonesia based on auditor quality and monetary unit of financial statement presentation. This research investigate 434 firms during the years 2012 to 2014. The results showed that 7.1 percent of the firmsrevaluation of assets and 92.9 percent have not been revalued their assets. Firms that revalued their assets, 3 percent of them audited public accountant firms affiliated with the Big 4 and 4.1 percent of them did not. The number of issuers that revalue assets and presents its financial statements in the rupiah currency as much as 5.3 percent and 1.8 percent in US dollars.